2002
DOI: 10.1046/j.1365-2400.2002.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the robustness of predictive yield models based on catchment characteristics using GIS for reservoir fisheries in Sri Lanka

Abstract: Land‐use patterns in the catchment areas of Sri Lankan reservoirs, which were quantified using Geographical Information Systems (GIS), were used to develop quantitative models for yield prediction. The validity of these models was evaluated through the application to five reservoirs that were not used in the development of the models, and by comparing with the actual fish yield data of these reservoirs collected by an independent body. The robustness of the predictive models developed was tested by principal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…These findings indicate that nutrient enrichment and trophic state are negatively influenced by RRLF . It is also well known that allochthonous nutrient enrichment into streams and reservoirs is influenced by land‐use patterns in stream/reservoir catchment areas (Amarasinghe, De Silva, & Nissanka, ; Borre, Barker, & Duker, ; Lenat & Crawford, ; Roth, Allan, & Erickson, ). Because this aspect was beyond the scope of the present study, only the possible influences of hydrological regimes on the water quality in the study irrigation reservoirs were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that nutrient enrichment and trophic state are negatively influenced by RRLF . It is also well known that allochthonous nutrient enrichment into streams and reservoirs is influenced by land‐use patterns in stream/reservoir catchment areas (Amarasinghe, De Silva, & Nissanka, ; Borre, Barker, & Duker, ; Lenat & Crawford, ; Roth, Allan, & Erickson, ). Because this aspect was beyond the scope of the present study, only the possible influences of hydrological regimes on the water quality in the study irrigation reservoirs were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Ranging from pioneer studies in fishery and aquaculture management (Meaden and Kapetsky, 1991) to recent applications in fisheries evaluation and planning (Amarasinghe et al, 2002;Isaak and Hurbert, 1997), the application of geographic information technologies has gradually increased in the fisheries management context (Close and Hall, 2006;Meaden, 2000). Anuchiracheeva et al (2003) showed that GIS was an important decision support tool to systematize, analyze, and display local knowledge in fisheries management at the community level in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…It can be foreseen that the assessment of fishery productivity based on GIS should be a new hotspot in future fishery researches [17,18] .…”
Section: Assessment Methodsmentioning
confidence: 99%